Labour Mobilities, Unemployment, Economic Development of the Central Asian Countries After Independence - Jumaev, Ergash (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyses the influence the evolution of the economic situation of the countries of Central Asia after they gained independence. In particular, the problems of labour mobility, unemployment and economic transformation, the formation of foreign economic activity, as well as the development of the migration policy of the Central Asian republics are considered. Object of attention of various actors of economic development.